Serum Total 25‐OH Vitamin D Adds Little Prognostic Value in Patients Undergoing Coronary Catheterization. Issue 10 (October 2016) - Gerling, Michael E.; James, Matthew T.; Wilton, Stephen B.; Naugler, Christopher; Southern, Danielle A.; Galbraith, P. Diane; Knudtson, Merril; de Koning, Lawrence
Abstract : Background: Vitamin D deficiency is associated with an increased risk of cardiovascular disease; however, it is unclear whether vitamin D status should be considered in clinical risk assessments of patients with cardiovascular disease. Methods and Results: This study included 2975 patients who had their first serum total 25‐hydroxy vitamin D (25‐OH vitamin D) measurement before their first coronary catheterization in Alberta, Canada. Cox regression was used to examine associations between 25‐OH vitamin D and mortality risk after adjusting for demographic and clinical risk factors. Interactions were tested using multiplicative terms, and prognostic value was assessed using measures of model discrimination, fit, calibration and net reclassification improvement. There were 401 deaths over a median of 5.8 years of follow‐up. Serum total 25‐OH vitamin D was inversely associated with mortality after adjusting for demographic and clinical risk factors, which was largely driven by excess risk in the bottom quintile (hazard ratio 1.84 for bottom versus top quintile, 95% CI 1.36–2.50, P for trend <0.001). Associations were weaker in the presence of several competing risk factors (e.g., advanced age; P for interactions <0.05). Adding 25‐OH vitamin D to a model containing demographic and clinical risk factors yielded similar discrimination, model fit, and calibration and only modest improvements in risk reclassification (net reclassification improvement 1.9% for deaths, 2.3% for survivors). Conclusions: Pre‐catheterization, serum total 25‐OH vitamin D was inversely associated with mortality risk after adjusting for established demographic and clinical risk factors. This association was attenuated by several competing risk factors. Overall, 25‐OH vitamin D added little prognostic value over established risk factors; therefore, its measurement is not warranted in patients undergoing coronary catheterization.